2010
DOI: 10.1590/s0100-06832010000300021
|View full text |Cite
|
Sign up to set email alerts
|

Response of Epidendrum Ibaguense (orchidaceae) to the application of lime rates to the pot

Abstract: In the best cultivation methods of orchids, in particular of the genus Phalaenopsis, liming is a common practice. The objective of this study was to evaluate the influence of lime rates (0.0; 1.0; 2.0; 3.0; 4.0; and 5.0 g dm -3 of substrate) applied to the cultivation substrate (xaxim) on the growth of Epidendrum ibaguense seedlings. In a greenhouse, 1-L plastic pots filled with 0.8 dm 3 of xaxim were irrigated such that no leachate was lost during the experiment. N, P, K, Ca, Mg, S, Fe, Zn, B, and Mn contents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…anceps. Rodrigues et al (2010b) reported a higher dry matter yield, number, and weight of leaves of Epidendrum ibaguense with different amounts of lime. Hsu et al (2010) reported that supplementation with calcium nitrate (300 mg·L −1 ) improved the quality of the inflorescences of Oncidium ʻGower Ramseyʼ.…”
Section: Mineral Fertilization and Biofertilization Differentially Afmentioning
confidence: 98%
“…anceps. Rodrigues et al (2010b) reported a higher dry matter yield, number, and weight of leaves of Epidendrum ibaguense with different amounts of lime. Hsu et al (2010) reported that supplementation with calcium nitrate (300 mg·L −1 ) improved the quality of the inflorescences of Oncidium ʻGower Ramseyʼ.…”
Section: Mineral Fertilization and Biofertilization Differentially Afmentioning
confidence: 98%
“…Zinc plays an important role for seedling metabolism and growth; according to some authors, its availability must be increased in culture medium for an enhancement of orchid in vitro growth (RODRIGUES et al, 2010). In this study, pyroligneous liquor may have acted as a nutrient source for protocorms due to its concentration of macro and micronutrients (Table 1).…”
Section: Figure 1 Protocorms Of Oeceoclades Maculata (Lindl) With Lmentioning
confidence: 91%
“…Fertilizers inhibited growth and development of the root while stimulating the stems and leaves. The plant grows under various conditions at altitudes of 0-1650 meters [21].…”
Section: Morphological Studymentioning
confidence: 99%